Dampak Perkembangan Pasar Modern di Lingkungan Pasar Tradisional di Mimbo Situbondo - M. Zikwan (Fakultas Ekonomi dan Bisnis Islam, 2020)
The market is a mechanism that can bring buyers together to make transactions on goods or services. The market is the most important part of a Muslim's life as an ideal transaction vehicle. In Indonesia the market is the economic support of society, both urban and rural communities. In terms of physical there are two types of markets in Indonesia, namely traditional markets and modern markets. Traditional market is a kind of market that is managed simply who still apply the bargaining system. While the modern market is a market that is managed with modern management that generally there dikinjagi sebaagi provider of goods or services with good quality of service to the consumer and the absence of bargaining process at the time of the transaction. At first these two types of markets supported each other in improving the economy of society, but in recent times the first type of market (traditional market) has often complained against the growth of so many modern markets. Departing from this problem the authors examine the problem that finally raised in the thesis with the title